Strategies for Management of Change in Educational Management at Basic Education: A case of schools in Phitsanulok - Kaewuraia, Wareerat; Panichpharinchai, Teamjan; Wattanathorn, Amornrat (Asian Health, Science and Technology Reports, 2010)
The research objectives of Strategies for Change Management in Educational Management at Basic Education: A case of schools in Phitsanulok were to 1) survey change management in educational management of schools 2) study method of change management in educational management by using focus group discussion 3) conclude and disseminate change management in educational management to schools. The theoretical framework concerns with Thawat Boonyamanee (2007) an essential component of change management to effective organization in 6 aspects; 1) goals and strategies 2) technology 3) job redesign 4) structure 5) process 6) people. The research methodology started with surveying change management in the 8 schools sample group, analyzing data from the first survey result and change management documents, meeting with focus group discussion process administrators who have selected cover with whole three Phitsanulok educational service area and three school sizes (big, medium, and small) from 14 schools for study method of change management in educational management, synthesizing strategy from the focus group discussion result, verifying validity of its strategy with initiated 14 administrators, managing meeting with seminar activity and present best practice schools in three different sizes to disseminate change management in educational management to administrators and teachers who is an agent whole three Phitsanulok educational service area, concluding research result and arranging research report. The research results revealed that; 1. The change management in educational management of schools has distinct in an essential component of change management to effective organization in 3 aspects; 1) structure 2) process 3) people but indistinct in 3 aspects 1) goals and strategies 2) job redesign 3) technology 2. The result of synthesizing change management in educational management strategy found that the successful of change management in educational management at basic education depend on having a vision and an academic leader of administrators, working cooperate participation with school stakeholder, and having principle for foundation to efficiency administration. 3. The result of seminar and disseminating found that strategy for change management in educational management has different to follow social context in each school however strategy for change management divided to 2 levels include goal strategy for schools’ change management idea to success goal and process strategy for means in encourage practice in school to the best of development for ready change.